EXERCISE-INDUCED MODULATION OF PAIN IN ADULTS WITH AND WITHOUT PAINFUL DIABETIC NEUROPATHY - Knauf, Matthew T. (J Pain, 2014)
The purpose of this study was to examine exercise-induced pain modulation in diabetic adults with painful diabetic neuropathy (PDN) compared to diabetic adults without PDN. Eighteen adults diagnosed with Type 2 diabetes with and without PDN (mean age of 49 yrs) completed two sessions. During the familiarization session, participants completed questionnaires, were familiarized with the pain testing protocols, and completed maximal isometric contractions. During the exercise session, experimental pain testing was completed before and following exercise consisting of three minutes of isometric exercise performed at 25% MVC. Ratings of perceived exertion (RPE) and muscle pain (MP) were assessed every 30 seconds during exercise. Results indicated RPE and MP during exercise were significantly higher (p < 0.05) for diabetic adults with PDN vs diabetic adults without PDN. Diabetic adults with PDN did not experience changes in thermal pain ratings following exercise while diabetic adults without PDN reported significantly lower pain ratings following exercise. It is concluded that diabetic adults with PDN experienced high levels of muscle pain during exercise and a lack of exercise-induced hypoalgesia following exercise in comparison to diabetic adults without PDN who experienced lower levels of muscle pain during exercise and a hypoalgesic response following exercise.